@FrostFlare23 mind showing the work you did to arrive at that answer?
alright give me a second
well techincally I did work but none of the answers matched mine
f(-3) = 2(-3) + 5
f(-3) = -6 + 5 = -1
did I screw up?
you there dude?
Looks right so far, but ...
You should calculate f(g(x)) first, then calculate f(g(-3)).
oh. uhm how do I do that? thats the only thing that confuses me
I'll get you started: f(x) = 2x + 5 1. Replace x with g(x) f(g(x)) = 2(g(x)) + 5 2. Replace g(x) with x - 7 = 2(x - 7) + 5 3. Simplify the expression
hmm... 2x -14 +5?
So f(g(x)) = 2x - 14 + 5, but that can also be further reduced, right?
I think so
Because -14 + 5 = -9 so f(g(x)) = 2x - 9 Now calculate f(g(-3))
hmm. so we would add 14 to both the 5 and the -14?
oh sorry. lol late comment there
@FrostFlare23 waiting on you ...
so we would then divide 2 to both sides to isolate the X in order to get x = 4.5?
No, you just simply evaluate f(g(x)) at x = -3 f(g(x)) = 2x - 9 f(g(-3)) = 2(-3) - 9
so basically it would become: 2(-3) which equals -6. then we subtract -6 from 9 to get -15?
ok so I was right I just ha the wrong way of doing it the first time thank you!
Both ways of doing it are correct. It's just better practice to write f(g(x)) as a single expression then evaluate it once.
alright thank you kind sir!
The problem with doing it the way is, if someone asked you what f(g(x)) is, you wouldn't be able to tell them.